Further Evidence on "Estimation of a Disequilibrium Aggregate Labor Market" - Yatchew, Adonis J. (The Review of Economics and Statistics, 1981)
that final demand of 55 units for commodity one generates 45.29 units of pollution, and final demand of 30 units for commodity two generates 18.44 units of pollution. From the appropriate elements in the last row of the inverse, we can calculate the coefficients of pollution generated per unit of final demand. These coefficients are 0.823 for commodity one and 0.615 for commodity two. It should be pointed out that the allocation of total pollution in (12) differs from that given by Leontief because he subdivides the total according to gross output figures rather than by final demand. REFERENCES